2020
DOI: 10.3390/rs13010054
|View full text |Cite
|
Sign up to set email alerts
|

ATSS Deep Learning-Based Approach to Detect Apple Fruits

Abstract: In recent years, many agriculture-related problems have been evaluated with the integration of artificial intelligence techniques and remote sensing systems. Specifically, in fruit detection problems, several recent works were developed using Deep Learning (DL) methods applied in images acquired in different acquisition levels. However, the increasing use of anti-hail plastic net cover in commercial orchards highlights the importance of terrestrial remote sensing systems. Apples are one of the most highly-chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…To summarize, our results indicate that VFNET provided the highest F1-Score, followed by RetinaNet, SABL, Faster R-CNN, and ATSS. Previous studies in remote sensing [49,50] showed that ATSS provided more accurate results for pole and apple detection; however, for active fire detection, ATSS provided less accurate results due to a small rate of True Positives, indicating the inability of the trained model (considering the same number of training epochs of the remaining algorithms) to identify active fire regions.…”
Section: Qualitative Analysis and Discussionmentioning
confidence: 93%
“…To summarize, our results indicate that VFNET provided the highest F1-Score, followed by RetinaNet, SABL, Faster R-CNN, and ATSS. Previous studies in remote sensing [49,50] showed that ATSS provided more accurate results for pole and apple detection; however, for active fire detection, ATSS provided less accurate results due to a small rate of True Positives, indicating the inability of the trained model (considering the same number of training epochs of the remaining algorithms) to identify active fire regions.…”
Section: Qualitative Analysis and Discussionmentioning
confidence: 93%
“…Feature extraction in the architecture of deep learning can be found in imaging applications. Different types of this architecture in deep learning that have frequently been applied in recent years are unsupervised pre-trained networks (UPNs), recurrent neural networks (RNNs) and convolutional neural networks (CNNs) [92]. An RNN has the advantage of processing time-series data and making decisions about the future based on historical data.…”
Section: Deep Learning For Image Annotationmentioning
confidence: 99%
“…When given sufficient data, the deep learning algorithm can generate and extrapolate new features without having to be explicitly told which features should be utilized and how they can be extracted [12][13][14]. CNNs (convolutional neural networks) are another variety of algorithm belonging to deep learning technology, which can provide insights into image-related datasets that we have not yet understood, achieving identification accuracies that sometimes surpass the human-level performance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%